Low friction of metallic multilayers by formation of a shear-induced alloy - Cihan, Ebru (Sci Rep, 2019)
During sliding of metallic surfaces, the near surfaces undergo significant changes in terms of topography, composition and microstructure. Since friction and wear behavior of the materials are strongly influenced by sub-surface deformations, it is fundamental to investigate these effects. Therefore, the present study aims towards a better understanding of the behavior of friction depending on well-defined initial microstructures. By performing sliding experiments on Au-Ni multilayer samples under ultrahigh vacuum (UHV) conditions, we observe that the individual layer thickness of multilayer systems has a strong influence on friction behavior due to the transition in the dominant deformation mechanism near the surface. The experiments reported here provide a new route for lowering the friction force of metallic material systems in dry contact by providing more stable microstructures and alloy formation. Through ultrafine grains present in the alloy formed by mechanical mixing the number of grain boundaries strongly increases and hence, grain boundary-mediated deformation results in the low friction coefficient.